Hydrogen Production Technologies: From Fossil Fuels toward Renewable Sources. A Mini Review - Megía, Pedro J; Vizcaíno, Arturo J; Calles, José A; Carrero, Alicia (Energy & fuels, 2021)
The global economic growth, the increase in the population, and advances in technology lead to an increment in the global primary energy demand. Considering that most of this energy is currently supplied by fossil fuels, a considerable amount of greenhouse gases are emitted, contributing to climate change, which is the reason why the next European Union binding agreement is focused on reducing carbon emissions using hydrogen. This study reviews different technologies for hydrogen production using renewable and non-renewable resources. Furthermore, a comparative analysis is performed on renewable-based technologies to evaluate which technologies are economically and energetically more promising. The results show how biomass-based technologies allow for a similar hydrogen yield compared to those obtained with water-based technologies but with higher energy efficiencies and lower operational costs. More specifically, biomass gasification and steam reforming obtained a proper balance between the studied parameters, with gasification being the technique that allows for higher hydrogen yields, while steam reforming is more energy-efficient. Nevertheless, the application of hydrogen as the energy vector of the future requires both the use of renewable feedstocks with a sustainable energy source. This combination would potentially produce green hydrogen while reducing carbon dioxide emissions, limiting global climate change, and, thus, achieving the so-called hydrogen economy.